2023
DOI: 10.1371/journal.pone.0281954
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant western diet and chronic-binge alcohol dysregulate hepatic metabolism

Abstract: Background and aims There is significant overlap between non-alcoholic fatty liver disease (NAFLD) and alcohol-associated liver disease (ALD) with regards to risk factors and disease progression. However, the mechanism by which fatty liver disease arises from concomitant obesity and overconsumption of alcohol (syndrome of metabolic and alcohol-associated fatty liver disease; SMAFLD), is not fully understood. Methods Male C57BL6/J mice were fed chow diet (Chow) or high-fructose, high-fat, high-cholesterol die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Interestingly recent studies reported that ethanol in drinking water and/or binge ethanol intake exacerbated liver injury in mice fed the Western diet (141,142), which is required further characterization.…”
Section: Alcohol-associated Liver Cancermentioning
confidence: 99%
“…Interestingly recent studies reported that ethanol in drinking water and/or binge ethanol intake exacerbated liver injury in mice fed the Western diet (141,142), which is required further characterization.…”
Section: Alcohol-associated Liver Cancermentioning
confidence: 99%
“…The study affirms that the Mediterranean diet has significant benefits in managing major chronic diseases such as cardiovascular disease, obesity, diabetes, and some types of cancer, based on its fundamental characteristics. Recently, there has been increasing recognition that the Mediterranean Diet, when combined with fitness along with cognitive behavior therapy, may serve as the optimal nutritional plan for preventing and treating NAFLD patients [72,73]. Moreover, the outcomes of multiple nutritional therapy studies have confirmed the advantageous impacts of the Mediterranean diet on non-alcoholic fatty liver disease (NAFLD).…”
Section: The Topic Of Interest Is the Relationship Between Metabolic ...mentioning
confidence: 99%